Low-temperature high-power discharge sodium battery and preparation method thereof
By using the combination technology of skeleton support materials, conductive fillers, optimized electrolytes, nano-positive positive and negative electrode materials and porous separators in sodium ion batteries, the problems of poor discharge performance, high impedance and short cycle life in low temperature environments are solved, and the low temperature electrochemical performance of high magnification and long cycle life is achieved.
Patent Information
- Application Number
- CN202510083114.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-22
AI Technical Summary
Existing sodium ion batteries exhibit poor discharge performance, high impedance and short cycle life in low temperature environments, limiting their application in cold areas and high-power energy storage scenarios.
The design of skeleton support materials combined with conductive fillers is used to optimize the electrolyte formulation, and the positive and negative electrode materials are improved by nano-treating treatment and surface coating modification technology. Porous diaphragms are prepared through wet stretching process to optimize the pore size and porosity of the diaphragms.
It significantly improves the electron transport capability and ion mobility of sodium batteries in low temperature environments, extends the cycle life, improves the high-rate discharge performance, and solves the problem of insufficient performance of batteries under low temperature conditions.
Smart Images

Figure CN119864494A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy storage technology, in particular to a low-temperature high-power discharge sodium battery and a preparation method thereof. Background Art
[0002] With the rapid development of new energy, energy storage technology plays an increasingly important role in power system peak and frequency regulation, new energy vehicle power source and portable electronic devices. As the current mainstream energy storage battery technology, lithium-ion batteries have certain advantages in energy density and cycle life, but their high cost, resource scarcity and rapid performance degradation in low temperature environments have severely restricted their development in large-scale energy storage and cold region applications.
[0003] Sodium-ion batteries are considered an alternative to lithium-ion batteries due to their low cost and abundant resources, and have attracted much attention in the field of energy storage. However, existing sodium-ion battery technology still faces many technical bottlenecks in practical applications, and these problems are particularly prominent in low-temperature environments, which affects its promotion and application in a wider range of fields.
[0004] One is the low-temperature stability of the electrolyte. The electrolyte of sodium-ion batteries is usually composed of high-melting-point sodium salts and carbonate solvents. Although these solvents have good ion conductivity at room temperature, in a low-temperature environment, the viscosity of the electrolyte increases significantly, and the solubility of the sodium salt and the ion migration ability decrease. At the same time, carbonate solvents are prone to crystallization or precipitation at low temperatures, resulting in a significant reduction in the conductivity of the electrolyte. This problem makes the discharge capacity and rate performance of existing sodium-ion batteries in low-temperature environments seriously insufficient. In addition, the compatibility problem between the electrolyte and the electrode interface is also more prominent under low-temperature conditions, and the interface film (such as the SEI film) is prone to uneven cracks or local collapse, which further increases the interface impedance and reduces the cycle stability of the battery.
[0005] The second is the problem of ion and electron transport of positive and negative electrode materials. The positive electrode materials (such as layered oxides, sodium iron phosphates, etc.) and negative electrode materials (such as hard carbon, titanium-based compounds) of sodium ion batteries generally have poor kinetic properties at low temperatures. Under low temperature conditions, the diffusion rate of sodium ions is significantly reduced, especially when the positive electrode particles are large or lack surface modification, the ion migration path is too long, causing the battery to exhibit obvious polarization during the charge and discharge process. In addition, the interfacial reaction process of the negative electrode material at low temperatures is also slow, and the interfacial impedance is significantly increased, affecting the embedding and de-embedding efficiency of sodium ions. Although there are many studies on the modification of positive and negative electrode materials in the prior art, there are still many limitations, such as insufficient optimization of material particle size, lack of surface conductive coating, etc., resulting in limited effect of improving rate performance.
[0006] The third is the structural design problem of the diaphragm. At present, the diaphragm materials widely used in sodium-ion batteries are mainly polypropylene and polyethylene. These diaphragms are relatively reliable in mechanical properties, but have poor ion conductivity at low temperatures. The pore size distribution and porosity of the diaphragm directly affect the wettability of the electrolyte and the ion migration path. The diaphragms in the prior art often have excessively large pores or uneven pore distribution, resulting in a decrease in the electrolyte penetration efficiency and an increase in the ion migration resistance. At the same time, an excessively large pore size may cause ion leakage, resulting in a decrease in electrochemical performance; and insufficient porosity may limit the storage of the electrolyte, further affecting the low-temperature performance.
[0007] Fourth, the overall impedance of the battery under low temperature conditions. The overall impedance of the sodium-ion battery is affected by multiple factors including the electrolyte, electrode materials, and diaphragm performance. Under low temperature conditions, the rapid increase in electrolyte impedance and interface impedance leads to a significant decrease in battery output power. At the same time, the polarization voltage increases rapidly, the discharge platform decreases, and the battery capacity decays severely. This problem is particularly prominent under high-rate discharge conditions. No effective overall solution has been proposed in the prior art, and it is difficult to form a systematic improvement from material design to structural optimization.
[0008] In summary, the performance of existing sodium-ion battery technology in low-temperature environments still has many limitations, which are specifically reflected in the poor low-temperature stability of the electrolyte, insufficient kinetic performance of the positive and negative electrode materials, unreasonable diaphragm structure design, and high overall impedance. These problems lead to significant capacity attenuation and short cycle life of sodium-ion batteries under low-temperature and high-rate discharge conditions, which restricts their application in cold areas and high-power energy storage scenarios. In order to solve the above technical bottlenecks, there is an urgent need for a sodium-ion battery design that has high-rate performance and long cycle life under low-temperature conditions. Summary of the invention
[0009] In view of the deficiencies in the prior art, the present invention provides a low-temperature, high-power discharge sodium battery and a preparation method thereof, which solves the problems of poor discharge performance, high impedance and short cycle life of the existing sodium ion batteries in a low temperature environment.
[0010] To achieve the above objectives, the present invention is implemented through the following technical solutions: A low-temperature high-power discharge sodium battery, comprising: A skeleton support material, which is composed of 60-85wt% of a polymer and 5-15wt% of a conductive filler; An electrolyte comprising 15-25 wt% of a high melting point sodium salt, 60-80 wt% of a low freezing point organic solvent and 1-5 wt% of an additive; A positive electrode material, which is sodium iron phosphate, layered oxide or Prussian blue compound, wherein the positive electrode material contains 80-95 wt % of active material and 2-8 wt % of conductive carbon coating; A negative electrode material, which is a hard carbon or titanium-based compound, wherein the negative electrode contains 90-98 wt % of active material and 2-5 wt % of binder; The diaphragm is made of porous polypropylene or polyethylene material, and its porosity is 35-55%.
[0011] Preferably, the polymer in the skeleton support material is polyvinylidene fluoride, polyimide or polyetheretherketone, and the conductive filler in the skeleton support material is surface modified nano-carbon fiber, carbon nanotube or graphene.
[0012] Preferably, the binder in the negative electrode material is polyvinylidene fluoride or polyacrylic acid.
[0013] Preferably, the organic solvent in the electrolyte includes 30-40 wt % of ethylene carbonate, 30-40 wt % of propylene carbonate and 20-30 wt % of diethyl carbonate.
[0014] Preferably, the additive in the electrolyte is fluoroethylene carbonate, sulfonimide compound or dimethyl sulfoxide.
[0015] Preferably, the particle size of the sodium iron phosphate particles is 1 to 5 μm, and the conductive carbon coating is graphene or carbon black, and the coating thickness is 1 to 3 μm.
[0016] Preferably, the particle size of the hard carbon particles in the negative electrode material is 10 to 20 μm, and the titanium-based compound in the negative electrode material is NaTi2(PO4)3 or TiO2.
[0017] Preferably, the separator is a porous membrane prepared by a wet stretching process, and the pore size is 0.2 to 0.5 μm.
[0018] A method for preparing a low-temperature, high-power discharge sodium battery comprises the following steps: Preparation of skeleton support material: disperse the polymer in an organic solvent, add a conductive filler, disperse by ultrasound for 30 to 60 minutes, pour the resulting suspension into a mold, dry at 60 to 80°C for 8 to 12 hours to solidify into a film; Preparation of electrolyte: dissolve high melting point sodium salt in organic solvent, add additives, stir at 40-60°C for 1-2h, and then filter; Preparation of positive and negative electrode materials: The active material of the positive electrode material is mixed with conductive carbon, a binder is added to make a slurry, and then coated on aluminum foil. The negative electrode material is hard carbon and a binder, which are coated on copper foil, dried separately and compacted; Assembly and injection: Place the diaphragm between the positive and negative electrodes, inject the electrolyte, and complete the packaging.
[0019] Preferably, in the step of preparing the positive and negative electrode materials, the thickness of the materials coated on the copper foil is 50-100 μm, the compaction pressure is 5-10 MPa, and the thickness of the electrodes after compaction is 30-50 μm.
[0020] The present invention provides a low-temperature, high-power discharge sodium battery and a preparation method thereof. It has the following beneficial effects: 1. The present invention adopts a design scheme of combining a skeleton support material with a conductive filler, uses a high thermal stability polymer to construct a matrix, and forms a nanoscale conductive network, which greatly reduces the internal resistance of the material and improves the electron transmission capacity in a low-temperature environment. Compared with the technical scheme in the prior art that polymer film materials cannot take into account both mechanical strength and conductive properties, the present invention effectively solves the problems of insufficient conductivity and poor low-temperature discharge performance, so that the sodium battery still has excellent electrochemical performance under low-temperature and high-rate conditions.
[0021] 2. The present invention optimizes the formula of the electrolyte. By selecting a composite system of a low-freezing-point organic solvent and a high-melting-point sodium salt and introducing an interface stabilizing additive, the ion mobility of the electrolyte at low temperatures and the stability of the electrode interface are improved. The high conductivity of the electrolyte at low temperatures ensures the cycle stability and safety of the battery at low temperatures.
[0022] 3. The present invention adopts nano-processing and surface coating modification technology of positive and negative electrode materials, which significantly improves the insertion / deinsertion kinetics of sodium ions. The conductive carbon coating on the surface of the positive electrode material optimizes the electron conduction path, and the negative electrode material uses the hard carbon disordered structure to provide rapid sodium insertion capability. Compared with the limitations of poor conductivity and insufficient rate performance of traditional battery positive and negative electrode materials, the present invention achieves higher discharge capacity and longer cycle life under low temperature and high power conditions, solving the deficiency of the prior art that cannot take into account both low temperature and high rate discharge performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram of the method flow of the present invention. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Please see attached Figure 1 The embodiment of the present invention provides a low-temperature high-power discharge sodium battery, comprising: A skeleton support material, which is composed of 60-85wt% of a polymer and 5-15wt% of a conductive filler; An electrolyte comprising 15-25 wt% of a high melting point sodium salt, 60-80 wt% of a low freezing point organic solvent and 1-5 wt% of an additive; A positive electrode material, which is sodium iron phosphate, layered oxide or Prussian blue compound, wherein the positive electrode material contains 80-95 wt% of active material and 2-8 wt% of conductive carbon coating; A negative electrode material, which is a hard carbon or titanium-based compound, containing 90-98 wt% of active material and 2-5 wt% of binder; The diaphragm is made of porous polypropylene or polyethylene material, and its porosity is 35-55%.
[0026] The polymer in the skeleton support material is polyvinylidene fluoride, polyimide or polyetheretherketone, and the conductive filler in the skeleton support material is surface modified nano-carbon fiber, carbon nanotube or graphene.
[0027] The binder in the negative electrode material is polyvinylidene fluoride or polyacrylic acid.
[0028] The organic solvent in the electrolyte includes 30-40 wt % of ethylene carbonate, 30-40 wt % of propylene carbonate and 20-30 wt % of diethyl carbonate.
[0029] The additive in the electrolyte is fluoroethylene carbonate, sulfonimide compound or dimethyl sulfoxide.
[0030] The particle size of the sodium iron phosphate particles is 1 to 5 μm, the conductive carbon coating is graphene or carbon black, and the coating thickness is 1 to 3 μm.
[0031] The particle size of the hard carbon particles in the negative electrode material is 10 to 20 μm, and the titanium-based compound in the negative electrode material is NaTi2(PO4)3 or TiO2.
[0032] The diaphragm is a porous membrane prepared by a wet stretching process, and the pore size is 0.2 to 0.5 μm.
[0033] A method for preparing a low-temperature, high-power discharge sodium battery comprises the following steps: Preparation of skeleton support material: disperse the polymer in an organic solvent, add a conductive filler, disperse by ultrasound for 30 to 60 minutes, pour the resulting suspension into a mold, dry at 60 to 80°C for 8 to 12 hours to solidify into a film; Preparation of electrolyte: dissolve high melting point sodium salt in organic solvent, add additives, stir at 40-60°C for 1-2h, and then filter; Preparation of positive and negative electrode materials: The active material of the positive electrode material is mixed with conductive carbon, a binder is added to make a slurry, and then coated on aluminum foil. The negative electrode material is hard carbon and a binder, which are coated on copper foil, dried separately and compacted; Assembly and injection: Place the diaphragm between the positive and negative electrodes, inject the electrolyte, and complete the packaging.
[0034] The thickness of the positive and negative electrode materials coated on the copper foil in the preparation step is 50-100 μm, the compaction pressure is 5-10 MPa, and the thickness of the electrode after compaction is 30-50 μm.
[0035] Example 1: Low-temperature sodium battery based on sodium iron phosphate positive electrode and hard carbon negative electrode Preparation of skeleton support material: Take 10g of polyvinylidene fluoride (PVDF) powder, add it to 100mL of N-methylpyrrolidone (NMP), stir for 30min to form a uniform suspension. Then add 1.5g of surface-modified nanocarbon fiber, use ultrasonic equipment to disperse for 40min, and set the power to 80W. Pour the suspension into a 10×10cm mold and dry it in an oven at 60℃ for 10h to obtain a skeleton support membrane. The thickness of the membrane after drying is about 50μm.
[0036] Preparation of electrolyte: Weigh NaPF6 and NaFSI in a ratio of 1:1, add to a mixed solvent (EC:PC:DEC = 1:1:1, volume ratio), the total mass fraction of sodium salt is 20wt%. Then add 3wt% of fluoroethylene carbonate (FEC) and 1wt% of sulfonimide compound, stir for 2h, and control the temperature at 50°C. After preparation, filter with a 0.2μm filter membrane to obtain a uniform electrolyte.
[0037] Preparation of positive electrode material: 9g of sodium iron phosphate (NaFePO4) active material was mixed evenly with 1g of graphene, and 2g of PVDF was added and dissolved in NMP to form a slurry. The slurry was coated on the aluminum foil current collector, dried and baked at 150℃ in a vacuum environment for 2h. After compaction, the positive electrode thickness was controlled at 40μm.
[0038] Preparation of negative electrode material: Weigh 9.5g of hard carbon, add 0.5g of polyacrylic acid (PAA) and appropriate amount of deionized water to form a uniform slurry. The slurry is coated on copper foil, dried naturally and placed in an oven at 100°C for 3h. Then, it is compacted with a pressure of 10MPa to obtain a negative electrode with a thickness of about 35μm.
[0039] Battery assembly: The prepared skeleton support material is used as a separator between the positive and negative electrodes, and the electrolyte is injected and packaged to form a button battery. The battery is used for testing after pre-cycling (0.1C current, 0°C, 2 cycles).
[0040] Example 2: Sodium battery based on Prussian blue positive electrode and titanium-based compound negative electrode Preparation of skeleton support material: 12g of polyimide (PI) powder was dissolved in 80mL of dimethylformamide (DMF) and stirred for 45min to form a solution. 2g of multi-walled carbon nanotubes (MWCNTs) were added and ultrasonicated for 1h with the power controlled at 90W to form a uniform dispersion. The dispersion was coated on the mold and dried at 70℃ for 12h to obtain a skeleton film with a thickness of about 45μm.
[0041] Preparation of electrolyte: 22 wt% NaBF4 was added to the solvent (EC:PC=1:1, volume ratio), and 2 wt% dimethyl sulfoxide (DMSO) was added as an antifreeze additive. The stirring temperature was 40°C, the time was controlled at 1.5 h, and then filtered to obtain a low-temperature electrolyte without crystallization.
[0042] Preparation of positive electrode material: Weigh 8g of Prussian blue compound Na2Fe[Fe(CN)6]·2H2O, mix with 2g of carbon black, add PVDF and NMP to form a uniform slurry. Coat it on the aluminum foil current collector, dry it at 100℃ in vacuum for 4h, and control the thickness of the positive electrode to 50μm after compaction.
[0043] Preparation of negative electrode material: 9g NaTi2(PO4)3 powder was mixed with 1g PVDF at a mass ratio of 9:1. The slurry was coated on the copper foil current collector and dried at 110°C for 3h. After drying, it was compacted with a pressure of 8MPa, and the thickness of the negative electrode was controlled to be 40μm.
[0044] Battery assembly: The above positive and negative electrode materials are used, the skeleton support film is used as the separator, and the electrolyte is injected to complete the packaging. The button battery is tested after the formation treatment (0.05C current, 2.5-3.8V, 3 cycles).
[0045] Example 3: High-rate sodium battery based on layered oxide positive electrode and hard carbon negative electrode Preparation of skeleton support material: Dissolve 10g of polyetheretherketone powder in 100mL of DMF and stir for 30min. Add 2g of graphene and use ultrasonic dispersion equipment for 50min with the power controlled at 100W. Pour the dispersion into the mold and dry at 80℃ for 10h to form a uniform skeleton membrane.
[0046] Preparation of electrolyte: Dissolve 20wt% NaPF6 in a mixed solvent (EC:PC:DEC=1:1:1, volume ratio) and add 3wt% fluoroethylene carbonate (FEC). Stir at 60°C for 2h. After stirring, filter to obtain a stable electrolyte.
[0047] Preparation of positive electrode materials: Take NaxNi 0·3 Co 0·3 Mn 0·49g of O2 active material was mixed with 1g of conductive carbon (carbon black), PVDF solvent was added to prepare the slurry, and then coated on aluminum foil. After natural drying, it was baked at 150℃ for 2h, and the positive electrode thickness was 45μm.
[0048] Preparation of negative electrode material: 10 g of hard carbon was weighed and mixed with PVDF at a mass ratio of 10:1 to form a slurry. The slurry was coated on a copper foil, dried at 120°C for 2 h, and compacted at a pressure of 10 MPa to obtain a negative electrode with a thickness of about 35 μm.
[0049] Battery assembly: Assemble the positive electrode, negative electrode and skeleton support membrane into a button battery, inject the electrolyte and then package it. The formation condition is 0.05C current (2~4V range).
[0050] Comparative Example 1: Skeleton support material without conductive filler (corresponding to Example 1) Preparation of skeleton support material: 10 g of polyvinylidene fluoride (PVDF) powder was added to 100 mL of N-methylpyrrolidone (NMP) and stirred for 30 min to form a uniform solution. The solution was directly poured into the mold without adding conductive filler. The mold was placed in a 60°C oven and dried for 8 h to obtain a film with a thickness of about 50 μm.
[0051] Preparation of electrolyte: Same as Example 1.
[0052] Preparation of positive and negative electrode materials: the same as in Example 1.
[0053] Battery assembly: The skeleton membrane without the conductive filler is used as a separator to assemble the battery, and the electrolyte is injected to complete the packaging. The formation conditions are the same as those in Example 1.
[0054] Comparative Example 2: No low temperature stabilizer is added to the electrolyte (corresponding to Example 2) Preparation of skeleton support material: same as Example 2.
[0055] Preparation of electrolyte: 22 wt% NaBF4 was added to a mixed solvent (EC:PC=1:1, volume ratio), and no low-temperature stabilizer (such as DMSO, FEC) was added. The stirring condition was maintained at 40°C for 1.5 hours and then filtered to obtain an electrolyte.
[0056] Preparation of positive and negative electrode materials: same as in Example 2.
[0057] Battery assembly: The assembly steps are the same as those in Example 2.
[0058] Comparative Example 3: The positive electrode material is not subjected to nano-processing (corresponding to Example 3) Preparation of skeleton support material: same as Example 3.
[0059] Preparation of electrolyte: Same as Example 3.
[0060] Preparation of positive electrode material: Take NaxNi with a normal particle size of 10 to 15 μm 0·3 Co 0·3 Mn 0·4 O2 (not nano-processed) was mixed with 1g of conductive carbon (carbon black), PVDF solvent was added to prepare the slurry, and then coated on aluminum foil. After drying, it was baked at 150℃ for 2h, and the positive electrode thickness was 45μm.
[0061] Preparation of negative electrode material: same as in Example 3.
[0062] Battery assembly: The assembly steps are consistent with Example 3.
[0063] Comparative Example 4: Negative electrode material without optimized binder ratio (corresponding to Example 1) Preparation of skeleton support material: same as in Example 1.
[0064] Preparation of electrolyte: Same as Example 1.
[0065] Preparation of positive electrode material: same as in Example 1.
[0066] Preparation of negative electrode material: 10g of hard carbon was mixed with 1g of PVDF (binder) in a ratio of 10:1 to form a slurry. The slurry was coated on copper foil and directly assembled into a negative electrode without compaction after drying. The thickness of the negative electrode was about 50μm.
[0067] Battery assembly: The assembly steps are the same as those in Example 1.
[0068] Comparative Example 5: Diaphragm pore size is too large (corresponding to Example 2) Preparation of skeleton support material: Take 12g of polyimide (PI) powder, dissolve it in 80mL of dimethylformamide (DMF), and stir for 45min. Add 2g of multi-walled carbon nanotubes (MWCNTs), ultrasonicate for 1h, control the power at 90W, and form a uniform dispersion. The dispersion is coated on the mold and dried at 70℃ for 12h to form a film with a thickness of about 45μm. During the wet stretching process, the pore size is controlled to be above 1μm.
[0069] Preparation of electrolyte: Same as Example 2.
[0070] Preparation of positive and negative electrode materials: same as in Example 2.
[0071] Battery assembly: The assembly steps are the same as those in Example 2.
[0072] Comparative Example 6: Insufficient sodium salt ratio in the electrolyte (corresponding to Example 3) Preparation of skeleton support material: same as Example 3.
[0073] Preparation of electrolyte: Dissolve 10wt% NaPF6 in a mixed solvent (EC:PC:DEC=1:1:1, volume ratio), but the optimal ratio is not reached. Add 3wt% fluoroethylene carbonate (FEC), control the stirring temperature at 60℃, and filter after 2h.
[0074] Preparation of positive and negative electrode materials: same as in Example 3.
[0075] Battery assembly: The assembly steps are consistent with Example 3.
[0076] Comparative Example 7: Positive Electrode Conductive Carbon Coating Not Optimized (Corresponding to Example 1) Preparation of skeleton support material: same as in Example 1.
[0077] Preparation of electrolyte: Same as Example 1.
[0078] Preparation of positive electrode material: 9g of sodium iron phosphate (NaFePO4) active material was directly mixed with a binder without adding conductive carbon to form a slurry, coated on an aluminum foil current collector, and baked at 150°C in a vacuum environment for 2h after drying. The thickness of the positive electrode was 40μm.
[0079] Negative electrode material preparation: same as in Example 1.
[0080] Battery assembly: The assembly steps are the same as those in Example 1.
[0081] Experiment 1: Experimental objective: To verify the effect of the introduction of conductive fillers in the skeleton support material on the discharge performance of the battery under low temperature conditions, especially the contribution to the internal resistance and low temperature rate discharge capacity of the battery.
[0082] Experimental samples: Example 1: The skeleton support material is PVDF (80 wt%) and surface modified carbon nanofiber (10 wt%), which are evenly dispersed to form a film.
[0083] Comparative Example 1: Only PVDF (100 wt %) was used without introducing a conductive filler.
[0084] Comparative Example 7: The skeleton support material is a PI (polyimide) film, and no conductive filler is introduced.
[0085] Comparative Example 4: The skeleton support material is PVDF+nano-carbon fiber, but the dispersion is uneven (ultrasonic dispersion time is shortened to 10 minutes).
[0086] Experimental methods and steps: Battery preparation: Positive electrode: NaFePO4 active material with a particle size of 5μm is used, mixed with conductive carbon (graphene) at a ratio of 9:1, PVDF is added to the slurry and then coated on aluminum foil, and then compacted to a thickness of 40μm after drying.
[0087] Negative electrode: hard carbon (particle size 10-20 μm) is mixed with PVDF at a ratio of 9:1, coated on copper foil, and compacted to a thickness of 35 μm after drying.
[0088] Electrolyte: NaPF6 (20 wt%) was dissolved in a mixed solvent of EC:PC:DEC (volume ratio 1:1:1), 3 wt% FEC was added, stirred evenly and then filtered.
[0089] Battery assembly: The positive and negative electrode materials are separated by different skeleton support materials (implementation examples or comparative examples), assembled into button batteries, injected with electrolyte, and packaged.
[0090] Test conditions: Discharge performance: At -20℃, perform constant current discharge at 1C rate, and record the discharge capacity and voltage platform.
[0091] Electrochemical impedance test: EIS is used to measure the AC internal resistance, with a frequency range of 10 6 ~10 -2 Hz, analyze the influence of skeleton support materials on ion conduction and electron transport.
[0092] Experimental data: Table 1: Effects of different skeleton support materials on discharge performance and internal resistance under low temperature conditions Summary: In Example 1, the skeleton support material constructs an excellent conductive network by introducing modified nano-carbon fibers, which significantly reduces the internal resistance of the battery. At -20°C, the discharge capacity of the sample reaches 122.8mAh / g, which is much higher than other comparative samples. At the same time, the internal resistance is controlled at 56.3Ω, which is more than 60% lower than that of comparative example 1 without adding conductive filler. It can be seen that nano-carbon fibers not only improve electron transmission in low temperature environments, but also optimize the microenvironment of ion migration.
[0093] In Comparative Example 1, only PVDF skeleton material is used. Due to its low electronic conductivity and ion permeability, the battery exhibits a high internal resistance and a low discharge capacity (92.4 mAh / g). This result reflects the defect that pure polymer skeleton support materials are difficult to meet the requirements of electronic and ion conduction at the same time. In Comparative Example 7, although the internal resistance is improved (118.2Ω) by replacing PI material, its low temperature performance is still inferior to that of Example 1 due to the lack of conductive filler. Although PI has excellent thermal stability, it lacks conductivity and cannot effectively improve the efficiency of electron transmission.
[0094] In addition, in Comparative Example 4, although nano-carbon fibers were added, the conductive network was broken in some areas due to uneven dispersion, resulting in a high internal resistance (88.4Ω) and the discharge capacity was not fully utilized. Compared with Example 1, the electron conduction efficiency inside the sample was greatly reduced. This result further illustrates that the uniform dispersion of nano-scale conductive fillers is crucial for optimizing the performance of the skeleton support material.
[0095] The experimental results confirmed from multiple perspectives that the design strategy of the skeleton support material is effective and unique. The introduction of nanocarbon fibers not only improves the overall conductivity of the skeleton membrane, but also improves the ion migration path under low temperature conditions through synergy with the PVDF matrix. This multi-level optimization mechanism is the core reason why the present invention surpasses the existing technology in low-temperature electrochemical performance.
[0096] Experiment 2: Experimental objective: To verify the effect of the introduction of low-temperature stabilizers (such as FEC, DMSO) in the electrolyte on the battery interface stability, low-temperature cycle life and electrochemical performance.
[0097] Experimental samples: Example 2: The electrolyte contains NaBF4 (22 wt%), low-temperature stabilizer FEC (3 wt%), and DMSO (1 wt%).
[0098] Comparative Example 2: The electrolyte contained only NaBF4 (22 wt%), without adding a low-temperature stabilizer.
[0099] Comparative Example 6: The proportion of NaPF6 in the electrolyte is only 10wt%, and no stabilizer is added.
[0100] Comparative Example 5: The electrolyte is NaPF6 (20 wt%), but does not contain FEC and DMSO.
[0101] Experimental methods and steps: Battery preparation: Positive electrode: Prussian blue compound Na2Fe[Fe(CN)6]·2H2O with a particle size of 2-4 μm was selected, mixed with carbon black at a ratio of 9:1, and then added to PVDF to form a slurry, which was coated on aluminum foil and compacted to a thickness of 50 μm after drying.
[0102] Negative electrode: NaTi2(PO4)3 active material is mixed with PVDF at a ratio of 9:1, coated on copper foil, and compacted to a thickness of 40μm after drying.
[0103] Electrolyte: Prepare electrolyte according to different formulas (examples or comparative examples), stir evenly and filter to ensure that there are no solid impurities.
[0104] Assembly: Use the same diaphragm to assemble the positive and negative electrodes and electrolyte into button batteries and complete the packaging.
[0105] Test conditions: Low temperature cycle life test: In a -20°C environment, charge and discharge at a 1C rate, and record the capacity retention rate after 200 cycles.
[0106] Observation of SEI layer morphology: After the test, the negative electrode was removed and the SEI layer morphology was observed using a scanning electron microscope (SEM).
[0107] Impedance test: Use EIS to measure battery impedance, frequency range 10 6 ~10 -2 Hz.
[0108] Analysis indicators: Capacity retention (cycle life).
[0109] The integrity and uniformity of the SEI layer.
[0110] The internal resistance of the battery.
[0111] Experimental data: Table 2: Effect of electrolyte formulation on low temperature cycle life and SEI layer stability Summary: The low-temperature cycle life test directly reveals the importance of low-temperature stabilizers for electrolytes. In Example 2, the stability of the SEI layer at the negative electrode interface was significantly improved by introducing FEC and DMSO, so that the capacity retention rate after 200 cycles reached 88.7%. In contrast, Comparative Examples 2, 5 and 6 all showed a phenomenon of rapid capacity decay, especially Comparative Example 6 (capacity retention rate was only 42.1%), exposing the serious effects of sodium salt concentration and lack of additives on electrolyte performance. From the data, the synergistic effect of FEC and DMSO not only reduces the interfacial impedance, but also optimizes the conduction path of ions at low temperatures.
[0112] In Comparative Example 2, no low-temperature stabilizer was added to the electrolyte. Although the sodium salt concentration was sufficient, the SEI layer on the surface of the negative electrode was unevenly covered and many cracks appeared. SEM observations showed that this unstable SEI structure may lead to low reaction efficiency of ions at the interface, continuous decomposition during the cycle, and greatly increased the internal resistance (148.5Ω). In Comparative Example 5, although the sodium salt concentration was reasonable, the lack of protective effects of additives such as FEC resulted in uneven coverage of the SEI layer and the interface morphology was still not ideal.
[0113] The excellent performance of Example 2 is due to the special effect of the low-temperature stabilizer. FEC, as an additive, can react with the negative electrode interface to form a high-strength and stable SEI film, reducing the interfacial reaction resistance of sodium ions. The introduction of DMSO further reduces the low-temperature crystallization tendency of the electrolyte and optimizes the migration rate of sodium ions. It is this dual mechanism that enables the battery to maintain a low impedance at -20°C and effectively prolongs the cycle life.
[0114] The test data of Comparative Example 6 verifies the important influence of sodium salt concentration on electrolyte conductivity from another perspective. 10wt% NaPF6 cannot provide sufficient ion concentration, resulting in violent negative electrode interface reaction and poor SEI layer formation, which directly leads to an impedance as high as 201.7Ω. In summary, the introduction of low-temperature stabilizers and the optimization of sodium salt concentration together constitute the core elements for improving electrolyte performance. The innovative design of the present invention in these two points gives it a significant advantage in low-temperature cycle stability.
[0115] Experiment 3: Experimental objective: To verify the effect of nano-processing of positive electrode materials and conductive carbon coating on battery rate performance, especially under low temperature and high rate discharge conditions.
[0116] Experimental samples: Example 3: The positive electrode material is nano-sized NaxNi 0·3 Co 0·3 Mn 0·4 O2, particle size 1-3 μm, surface coated with graphene conductive carbon (coating thickness 2 μm).
[0117] Comparative Example 3: The positive electrode material is NaxNi without nano-treatment 0·3 Co 0·3 Mn 0·4 O2, particle size is 10-15μm, no coating.
[0118] Comparative Example 7: The positive electrode material is nano-NaxNi without conductive carbon coating 0·3 Co 0·3 Mn 0·4 O2, particle size is 1 to 3 μm.
[0119] Comparative Example 1: The positive electrode material is sodium iron phosphate (NaFePO4) with a particle size of 5 μm and is not coated with conductive carbon.
[0120] Experimental methods and steps: Battery preparation: Positive electrode: According to the positive electrode material preparation method of different samples (nano-processing, conductive carbon coating, etc.), the active material and PVDF are mixed at a mass ratio of 90:10, slurried and coated on aluminum foil. After drying, it is baked at 150℃ in a vacuum environment for 2h and compacted to a thickness of 45μm.
[0121] Negative electrode: Hard carbon was used as the negative electrode material, mixed with PVDF at a ratio of 9:1, coated on copper foil, and compacted to a thickness of 35 μm after drying.
[0122] Electrolyte: NaPF6 (20 wt%) was dissolved in a mixed solvent of EC:PC:DEC (volume ratio 1:1:1), 3 wt% FEC was added, and the mixture was stirred evenly and then filtered.
[0123] Assembly: Assemble the positive and negative electrode materials, separator and electrolyte into button batteries and complete the packaging.
[0124] Test conditions: Rate performance test: At -10℃, constant current discharge tests were performed at 0.5C, 1C, 5C and 10C rates, and the discharge capacity and voltage platform were recorded.
[0125] Polarization performance test: Through constant current charging and discharging, the charge and discharge voltage difference at different rates is measured to evaluate the polarization phenomenon.
[0126] Electrode interface morphology: After the test, the positive electrode material was taken out and the integrity and morphology of the conductive layer on the surface of the particles were observed using SEM.
[0127] Analysis indicators: rate performance curve (rate-capacity relationship); electrode polarization voltage (charge and discharge voltage difference); positive electrode interface coating uniformity and structural stability.
[0128] Experimental data: Table 3: Effect of cathode material treatment on rate performance and polarization voltage Summary: The results of Example 3 clearly demonstrate the effect of nano-processing and conductive coating on the improvement of the performance of positive electrode materials. In the rate range of 0.5C to 10C, the sample always maintains a high capacity, especially at 10C it can still reach 125.2mAh / g. This performance is mainly attributed to the fact that the nano-sized positive electrode particles greatly shorten the sodium ion diffusion path and provide a larger specific surface area. The coated graphene conductive layer forms an efficient electronic conduction network, which significantly reduces the polarization phenomenon during the charge and discharge process. Its electrode polarization voltage is only 0.32V, which is much lower than other comparative examples.
[0129] In Comparative Example 3, the non-nano-sized positive electrode material showed obvious rate performance deficiency, especially the capacity dropped rapidly at high rates (5C, 10C). This phenomenon can be explained from the relationship between the particle size of the material and the electron conduction path. The large particles of 10-15 μm significantly limit the diffusion efficiency of sodium ions. At the same time, due to the poor conductivity between particles, the electrode polarization is severe at high rates, resulting in a significant reduction in the discharge voltage platform.
[0130] Although Comparative Example 7 uses nanosized particles, the electron conduction path between the positive electrode particles is not continuous because the conductive layer is not coated, and the interface impedance is high. The rate performance is slightly better than that of Comparative Example 3, but the capacity decrease is still significant at high rate (10C). This shows that simple particle nano-sizing cannot completely solve the rate performance problem, and the introduction of a conductive layer is an important supplement to improve the rate performance.
[0131] As for Comparative Example 1, the positive electrode material is traditional sodium iron phosphate (NaFePO4), which has poor rate performance due to its inherent insufficient conductivity and ion diffusion performance, especially at high rates (5C, 10C). The overall capacity is much lower than that of nano-layered oxide positive electrode materials. It can be seen that the structure and surface treatment of the positive electrode material are the key factors that determine the rate performance of the battery, and the present invention effectively overcomes this limitation through the coordinated design of nano-sizing and conductive coating, providing a more competitive solution for high-rate batteries.
[0132] Experiment 4: Experimental objectives: To verify the effect of binder optimization in negative electrode materials on electrode adhesion, structural stability and low-temperature cycle performance, and to analyze the effect of optimizing the binder ratio and type on electrochemical performance.
[0133] Experimental samples: Example 1: The negative electrode material is hard carbon (particle size 10-20 μm), and the binder is PVDF+PAA (9:1).
[0134] Comparative Example 4: The negative electrode material is hard carbon, the binder is PVDF (10 wt%), and there is no optimized ratio.
[0135] Comparative Example 3: The negative electrode material is hard carbon, and the binder is PVDF+CMC (9:1).
[0136] Comparative Example 6: The negative electrode material is hard carbon, and the binder is PVDF (10 wt%), but no compaction treatment is performed after coating.
[0137] Experimental methods and steps: Battery preparation: Negative electrode material: The negative electrode slurry is prepared according to different binder formulas. The negative electrode material is hard carbon. The slurry is coated on the copper foil and then dried naturally for subsequent treatment: Example 1: After drying, the film was compacted at a pressure of 10 MPa, and the final thickness was 35 μm.
[0138] Comparative Example 4: PVDF was used as the only binder and compacted to 40 μm.
[0139] Comparative Example 3: The binder is PVDF and CMC (9:1), compacted to 38 μm.
[0140] Comparative Example 6: Only PVDF was used as a binder without compaction treatment, and the thickness was 45 μm.
[0141] Positive electrode material: Sodium iron phosphate (NaFePO4) is uniformly used, mixed with PVDF at a ratio of 9:1 and coated on aluminum foil, and then compacted to a thickness of 40μm after drying.
[0142] Electrolyte: A unified mixed electrolyte of NaPF6 (20wt%) + FEC.
[0143] Test conditions: Peel force test: Use a tensile tester to measure the peel force of the electrode coating at a tensile rate of 1 mm / min (unit: N / cm 2 ).
[0144] Cycle life test: Charge and discharge at 1C rate at 0°C, and record the capacity retention rate after 200 cycles.
[0145] Microstructure observation: After the test, the negative electrode was taken out and the coating cracks and adhesion morphology were observed using SEM.
[0146] Analysis index: peeling force (N / cm 2 ); capacity retention rate (cycle stability); integrity of coating surface cracks and morphology.
[0147] Experimental data: Table 4: Effect of binder optimization on negative electrode adhesion and cycle performance Summary: Example 1 added PAA to the binder to form a reasonable 9:1 ratio with PVDF. This optimization significantly improved the adhesion of the coating (4.6 N / cm 2 ). The strong adhesion effectively reduces the coating peeling and crack generation during the cycle process, making the capacity retention rate reach 87.2% after 200 cycles. SEM observation shows that the negative electrode surface is flat and has no obvious cracks. Obviously, this binder combination not only strengthens the mechanical bonding force, but also improves the structural integrity of the negative electrode under low temperature conditions.
[0148] The results of Comparative Example 4 reflect the limitations of a single binder (PVDF). Although PVDF has a certain degree of flexibility, it is easy to form cracks during the cyclic charge and discharge process, resulting in a significant decrease in the peel force (2.1N / cm 2 ). This structural defect causes the coating to gradually fall off under long-term electrochemical reactions, hindering the conduction of electrons and ions, and ultimately leading to rapid capacity decay, with only 62.5% remaining after 200 cycles. This is further verified by the SEM results of cracks and peeling on the negative electrode surface.
[0149] Although the adhesive of Comparative Example 3 uses a combination of PVDF and CMC, the peeling force is slightly higher than that of Comparative Example 4, but still not as good as that of Example 1 (3.8 N / cm 2 In addition, there are local cracks on the coating surface, resulting in a capacity retention rate of only 74.8%. The problem of comparative example 6 is more obvious. Because no compaction treatment was performed, the surface of the negative electrode coating is uneven and the adhesion is the worst (1.5N / cm 2 ). Obviously, the lack of compaction process directly led to severe peeling of the coating during the cycle.
[0150] From a mechanistic analysis, the introduction of PAA significantly improves the mechanical properties of the PVDF binder. As a polymer acid, PAA enhances the tensile strength and flexibility of the coating through interaction with PVDF. In the electrochemical reaction, this flexible combination reduces the crack propagation caused by volume change in the coating. In addition, the compaction process further compresses the gaps between the particles and optimizes the transmission channels of electrons and ions. It can be seen that the optimized design and compaction treatment of the binder in Example 1 are important foundations for ensuring low-temperature cycle stability. These designs together give the present invention significant advantages in low-temperature and high-rate environments, overcoming the limitations of insufficient adhesive adhesion and easy detachment of the coating in the prior art.
[0151] Experiment 5: Experimental objectives: To study the effect of the diaphragm pore size on the electrolyte wettability and low-temperature impedance of the battery, and to evaluate the role of pore size optimization and uniformity on ion conductivity performance.
[0152] Experimental samples: Example 2: The diaphragm has a pore size of 0.2-0.5 μm, is prepared by a wet stretching process, and has a porosity of 40%.
[0153] Comparative Example 5: The pore size of the diaphragm is greater than 1 μm, the porosity is the same (40%), but the pore size is not optimized.
[0154] Comparative Example 6: The diaphragm was not subjected to wet stretching treatment, the pore size distribution was uneven, and there were a large number of macropores > 2 μm.
[0155] Example 1: The diaphragm and the skeleton support material are designed as an integrated whole, with a pore size of about 0.3 μm and a porosity of 35%.
[0156] Experimental methods and steps: Battery preparation: Positive electrode: Sodium iron phosphate (NaFePO4) is mixed with PVDF at a ratio of 9:1 to make a slurry, which is coated on aluminum foil and compacted to a thickness of 40μm after drying.
[0157] Negative electrode: Use hard carbon with a particle size of 10-20 μm, mix it with PVDF at a ratio of 9:1 and coat it on copper foil. After drying, compact it to a thickness of 35 μm.
[0158] Diaphragm: Batteries are assembled separately according to the separator formula of different samples.
[0159] Electrolyte: A mixed electrolyte of NaPF6 (20wt%) + FEC (3wt%) was uniformly used.
[0160] Test conditions: Wettability test: drop the electrolyte on the surface of the diaphragm and record the time (in seconds) required for the electrolyte to completely wet the diaphragm.
[0161] Low temperature impedance test: The internal resistance is measured by electrochemical impedance spectroscopy (EIS) at -30°C, with a frequency range of 10 6 ~10 -2 Hz.
[0162] Cycle performance test: At -20°C, charge and discharge at a rate of 1C, and record the capacity retention rate after 100 cycles.
[0163] Analysis indicators: electrolyte infiltration time; internal resistance (Ω); cycle capacity retention rate.
[0164] Experimental data: Table 5: Effect of diaphragm pore size on electrolyte wettability and low temperature impedance Summary: The optimization of the pore size of the diaphragm plays a key role in the wettability and ion conductivity of the electrolyte. In Example 2, the pore size of the diaphragm is strictly controlled within the range of 0.2 to 0.5 μm, and the uniformity of the pore structure is ensured by a wet stretching process. This design enables the electrolyte to quickly infiltrate the surface and spread completely in only 2.8 seconds, while effectively reducing the impedance (72.5Ω) under low temperature conditions. In the cycle performance test, the sample exhibited a capacity retention rate of 85.3%, far exceeding other comparative samples. Obviously, the synergistic optimization of pore size and uniformity greatly improves the compatibility of the electrolyte and the diaphragm.
[0165] In Comparative Example 5, the diaphragm pore size is too large (above 1 μm). Although the porosity is the same, the presence of macropores causes the electrolyte infiltration time to be extended to 8.4 seconds. The macroporous structure has a negative impact on the distribution uniformity of ion channels, causing the impedance of the battery at -30°C to increase significantly (134.8Ω). From the perspective of cycle performance, the capacity retention rate of this sample is only 61.7%, indicating that the excessively large pore size cannot provide an efficient path for ion migration in a low temperature environment.
[0166] The problem of comparative example 6 is more prominent. Because the wet stretching treatment was not performed, the pore size distribution of the diaphragm was uneven, and there were a large number of pores >2μm. The electrolyte penetration time on the surface was significantly prolonged (11.2 seconds), and the internal resistance under low temperature conditions reached 189.3Ω. This uneven pore structure directly led to the discontinuity of the ion channel, severely limiting the efficiency of ion migration, and ultimately leading to a decrease in cycle performance, with a capacity retention rate of only 50.2%.
[0167] Example 1 controls the pore size at 0.3μm through the integrated design of the skeleton support material, and the porosity is slightly lower than that of Example 2 (35%). Although the electrolyte infiltration time is slightly longer than that of Example 2 (3.6 seconds), its low-temperature impedance is still at a low level (84.7Ω). In terms of cycle performance, the capacity retention rate of this sample is 80.4%, showing a high low-temperature adaptability. This shows that the coordinated optimization of pore size control and skeleton support materials can also significantly improve ion migration performance.
[0168] The experimental results show that the reasonable control and uniformity of the diaphragm pore size are important factors in improving the performance of low-temperature batteries. The pore size optimization strategy of Example 2 significantly reduces the internal resistance and enhances the electrolyte wettability, which is directly related to the continuity of the ion migration path. Diaphragms with excessively large or uneven pore sizes expose higher impedance and capacity attenuation, further proving that the optimized design of the present invention can effectively solve the adverse effects of diaphragm structural defects on low-temperature performance in the prior art.
[0169] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A low-temperature, high-power discharge sodium battery, characterized in that: include: A skeleton support material, which is composed of 60-85wt% of a polymer and 5-15wt% of a conductive filler; An electrolyte comprising 15-25 wt% of a high melting point sodium salt, 60-80 wt% of a low freezing point organic solvent and 1-5 wt% of an additive; A positive electrode material, which is sodium iron phosphate, layered oxide or Prussian blue compound, wherein the positive electrode material contains 80-95 wt % of active material and 2-8 wt % of conductive carbon coating; A negative electrode material, which is a hard carbon or titanium-based compound, wherein the negative electrode contains 90-98 wt % of active material and 2-5 wt % of a binder; The diaphragm is made of porous polypropylene or polyethylene material, and its porosity is 35-55%.
2. A low-temperature, high-power discharge sodium battery according to claim 1, characterized in that: The polymer in the skeleton support material is polyvinylidene fluoride, polyimide or polyetheretherketone, and the conductive filler in the skeleton support material is surface modified nano-carbon fiber, carbon nanotube or graphene.
3. A low-temperature, high-power discharge sodium battery according to claim 1, characterized in that: The binder in the negative electrode material is polyvinylidene fluoride or polyacrylic acid.
4. A low-temperature, high-power discharge sodium battery according to claim 1, characterized in that: The organic solvent in the electrolyte includes 30-40 wt % of ethylene carbonate, 30-40 wt % of propylene carbonate and 20-30 wt % of diethyl carbonate.
5. A low-temperature, high-power discharge sodium battery according to claim 1, characterized in that: The additive in the electrolyte is fluoroethylene carbonate, sulfonimide compound or dimethyl sulfoxide.
6. A low-temperature, high-power discharge sodium battery according to claim 1, characterized in that: The particle size of the sodium iron phosphate particles is 1 to 5 μm, and the conductive carbon coating is graphene or carbon black, and the coating thickness is 1 to 3 μm.
7. A low-temperature, high-power discharge sodium battery according to claim 1, characterized in that: The particle size of the hard carbon particles in the negative electrode material is 10 to 20 μm, and the titanium-based compound in the negative electrode material is NaTi2(PO4)3 or TiO2.
8. A low-temperature, high-power discharge sodium battery according to claim 1, characterized in that: The separator is a porous membrane prepared by a wet stretching process, and the pore size is 0.2-0.5 μm.
9. A method for preparing a low-temperature, high-power discharge sodium battery, characterized in that: The following steps are involved: Preparation of skeleton support material: disperse the polymer in an organic solvent, add a conductive filler, disperse by ultrasound for 30 to 60 minutes, pour the resulting suspension into a mold, dry at 60 to 80°C for 8 to 12 hours to solidify into a film; Preparation of electrolyte: dissolve high melting point sodium salt in organic solvent, add additives, stir at 40-60°C for 1-2h, and then filter; Preparation of positive and negative electrode materials: The active material of the positive electrode material is mixed with conductive carbon, a binder is added to make a slurry, and then coated on aluminum foil. The negative electrode material is hard carbon and a binder, which are coated on copper foil, dried separately and compacted; Assembly and injection: Place the diaphragm between the positive and negative electrodes, inject the electrolyte, and complete the packaging.
10. The method for preparing a low-temperature, high-power discharge sodium battery according to claim 9, characterized in that: The thickness of the positive and negative electrode materials coated on the copper foil in the preparation step is 50-100 μm, the compaction pressure is 5-10 MPa, and the thickness of the electrode after compaction is 30-50 μm.
Citation Information
Patent Citations
Preparation method of battery diaphragm with high lithium ion conductivity
CN116315421A
Low-temperature low-density sodium ion battery electrolyte and sodium ion battery
CN117810542A
Ultralow-temperature high-rate sodium ion battery and preparation method thereof
CN119297428A
Finely porous polyolefin-based separator for secondary battery
JP2000212323A
Non-aqueous electrolyte secondary cell
US20030118896A1